The IMPACT OF INTERACTIVE LEARNING ACTIVITIES ON STUDENTS’ MOTIVATION IN LEARNING ENGLISH - Muh. Arfah Fauzi Ochi; Rizkariani Sulaiman; Hadijah (e-Journal of ELTS (English Language Teaching Society), 2026)
Students’ low motivation in learning English in Makassar, especially at the junior high school level, is often caused by monotonous traditional teaching methods that are less engaging. Limited variation in teaching strategies and the pressure of national examinations often lead to low motivation and reduced participation. This study aimed to identify interactive learning activities, particularly ice breaking and games, used in English classes, describe students’ perceptions, and analyze differences in students’ motivation before and after their implementation. A quasi-experimental design with a control group pre-test and post-test was conducted at SMPN 10 Makassar for one month using two classes. Data were collected through questionnaires, observation sheets, pre-tests, and post-tests and analyzed using SPSS. The results showed that the experimental group’s mean score increased from 67.50 (pre-test) to 79.90 (post-test) with a significance value of 0.000 (<0.05), indicating a significant improvement in students’ intrinsic motivation.